THE ROLE OF EDUCATION AND EDUCATION IN ELIMINATING THE IMPACT OF THREATS TO NATIONAL SPIRITUALITY - Bayeshanov Abdulla (Academia Science Repository, 2023)
In this article, the spiritual threats to our national spirituality, which are increasing in the process of globalization, and the issue of their elimination, are highlighted. In this way, the importance of education and upbringing, the role of the scientific and artistic heritage of our ancestors is revealed.